Characteristics of gastric and duodenal mucosa in the patients with primary biliary cholangitis - Popović, Dragana; Zgradić, Sanja; Dragašević, Sanja; Zec, Simon; Micev, Marijan; Naumović, Tamara; Milosavljević, Tomica; Milovanović, Tamara (Vojnosanitetski pregled, 2021)
Background/Aim. Primary biliary cholangitis (PBC) is an immune-mediated chronic cholestatic disease of liver, with a slow progression. The aim of our study was to determine the correlation of PBC, atrophic gastritis (AG) and gluten-sensitive enteropathy (GSE), to identify the macroscopic and histopathological modifications of gastric and duodenal mucosa which occur in PBC and to analyze the frequency of these changes compared to a control group. Methods. This study included 50 patients with PBC and 46 control subjects with the dyspeptic symptoms, without liver disease. All of the examined subjects underwent esophagogastroduodenoscopy. Macroscopic and histopathological findings of the gastric and duodenal mucosal samples were recorded and analyzed. Results. There was no statistically significant association between the PBC and AG, or between the PBC and Helicobacter pylori infection. There was a highly significant difference in the frequency of Helicobacter pylori infection and the presence of GSE in the patients in the control group compared to those with PBC. Conclusions. The patients with PBC are at a lower risk for Helicobacter pylori infectionand atrophic gastritis. Testing for GSE in the PBC patients may be beneficial, considering the higher incidence of GSE amongst these patients. GSE represents a risk factor for the presence of PBC and the patients with GSE are nearly four times more likely to have PBC.
Keywords: liver cirrhosis, biliary; gastritis, atrophic; glutens; celiac disease; comorbidity; histology; helicobacter pylori.